2014
DOI: 10.1139/er-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

Using pollutant release and transfer register data in human health research: a scoping review

Abstract: Pollutant release and transfer registers (PRTRs) collect and provide information on chemicals released to the environment or otherwise managed as waste. They support the public's right-to-know and provide useful information in gauging performance of facilities, sectors, and governments. The extent to which these data have been used in research, particularly in relation to human health, has not been documented. In this scoping review our objective was to learn from scholarly literature the extent and nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…To our knowledge, this is one of very few studies that utilize a national pollutant registry to explore multipollutant groups of industrial emissions and their potential relation to CHD [19].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is one of very few studies that utilize a national pollutant registry to explore multipollutant groups of industrial emissions and their potential relation to CHD [19].…”
Section: Discussionmentioning
confidence: 99%
“…The study of childhood cancer in areas surrounding environmental pollution sources is beginning to assume growing importance (Boothe et al, 2014;Heck et al, 2013a;Kheifets et al, 2015;Shrestha et al, 2014;Weng et al, 2008), and industrial pollution emission registers, such as E-PRTR, afford a very useful tool for the surveillance and monitoring of possible effects of industrial pollution on the health of the children (Wine et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research studies, mainly focusing on monitored urban pollutants, have identified linkages between environmental exposures, and fetal and early childhood deleterious effects, along with genetic, physical, social, dietary and biological factors [10]. However, the contribution of industrial pollution has not been fully explored [11], even though some of those chemicals are known to be developmental toxicants. This knowledge gap is even broader when assessing the role of mixtures of chemicals.…”
Section: Introductionmentioning
confidence: 99%